The Availability of Infrastructure in Townships: Is there Hope for Township Businesses? - Cant, Michael C. (International Review of Management and Marketing, 2017)
Townships are part and parcel of the business landscape in South Africa although it was started during the apartheid era in South Africa. The impact of the apartheid era is still evident in the townships and is a testimony of abandonment, poor investment, overpopulation and isolation from urban areas and a serious lack of infrastructure and necessary resources in these areas (Thulo, 2015). A significant amount (60%) of the unemployed comes from townships and informal settlements (Thulo, 2015). It is evident that townships are complex and integrated at the same time with poor and middle class communities living side by side. Government has been attempting to kick start the economy and in the process to increase employment through small businesses and the generation of jobs in townships. This process is however hampered by a range of factors including a lack of infrastructure. The research highlighted the serious shortcomings in infrastructures throughout South Africa, and a need for advisory centres were indicated as being the most dire need in these areas to assist small business. Keywords: infrastructure; SMEs; small businesses; township businesses; South Africa JEL Classifications: M00, M10